Pretreatment for reverse osmosis desalination - Voutchkov, Nikolay (Elsevier, 2017)
Pretreatment for Reverse Osmosis Desalination is a comprehensive reference on all existing and emerging seawater pretreatment technologies used for desalination. The book focuses on reverse osmosis membrane desalination, which at present is the most widely applied technology for the production of fresh drinking water from highly saline water sources (brackish water and seawater). Each chapter contains examples illustrating various pretreatment technologies and their practical implementation.